Broad geographical circulation of a novel vesiculovirus in bats in the Mediterranean region - Luo, Dong-Sheng; Harazim, Markéta; Maufrais, Corinne; Bonas, Simon; Martinkova, Natalia; Lalis, Aude; Nakouné, Emmanuel; Adjogoua, Edgard Valéry; Douno, Mory; Kadjo, Blaise; López-Roig, Marc; Pikula, Jiri; et al. (PLoS neglected tropical diseases, 2025)
Bats are the natural reservoirs for a variety of emerging and re-emerging viruses. Among them, rabies virus (genus Lyssavirus, family Rhabdoviridae) is one of the first and most emblematic described in these animals. Since its first description, several new bat lyssaviruses have been regularly identified. In addition to lyssaviruses, other bat rhabdoviruses have also been discovered, including members of the genera Vesiculovirus, Ledantevirus and, more recently, Alphanemrhavirus and Tupavirus. However, the family Rhabdoviridae is one of the most abundant and diverse viral families, with 434 officially recognized species, divided into 5 subfamilies and 56 different genera. The number of rhabdoviruses associated with bats is therefore probably higher than that currently available. In this study, we first developed and validated a combined nested RT-qPCR technique (pan-rhabdo RT-nqPCR) dedicated to the broad detection of animal rhabdoviruses. After validation, this technique was used for a large retrospective screening of archival bat samples (n = 1962), including blood (n = 816), brain (n = 723) and oral swab (n = 423). These samples were collected from various bat species over a 12-year period (2007-2019) in 9 different countries in Europe and Africa. A total of 23 samples (1.2%) from bat species Miniopterus schreibersii, Rhinolophus euryale and Rhinolophus ferrumequinum tested positive for rhabdovirus infection, including 17 (2.1%) blood and 6 (1.4%) oral swab samples, all collected from bats originating from the Mediterranean region. Complete virus genome sequences were obtained by next-generation sequencing for most of the positive samples. Molecular and phylogenetic analysis of these sequences demonstrated that the virus isolates, named Mediterranean bat virus (MBV), were closely related and represented a new species, Mediterranean vesiculovirus, within the genus Vesiculovirus. MBV was more specifically related to other bat vesiculoviruses previously described from China and North America, together clustering into a distinct group of bat viruses within this genus. Interestingly, our results suggest that MBV is widespread, at least in the western part of the Mediterranean region, where it circulates in the blood of several bat species. These results expand the host range and viral diversity of bat vesiculoviruses, and pave the way for further studies to determine the transmission route and dissemination dynamics of these viruses in bat colonies, as well as to assess their potential threat to public health.
Keywords: Phylogeny; infekce viry z čeledi Rhabdoviridae; genom virový; fylogeneze; Středomoří; Animals; Mediterranean Region; Genome, Viral; kvantitativní polymerázová řetězová reakce; Real-Time Polymerase Chain Reaction; Chiroptera; zvířata; Vesiculovirus; Rhabdoviridae Infections